Room temperature ferromagnetism and thermoelectric behavior of calcium based spinel chalcogenides CaZ2S4 (Z = Ti, V, Cr, Fe) for spintronic applications. (August 2022) - Mahmood, Q.; Nazir, Ghazanfar; Alzahrani, Jameela; Kattan, Nessrin A.; Al-Qaisi, Samah; Albalawi, Hind; Mera, Abeer; Mersal, Gaber A.M.; Ibrahim, Mohamed M.; Amin, Mohammed A.
Abstract: The electronic, magnetic, and thermoelectric properties of CaZ2 S4 (Z = Ti, V, Cr, Fe) are explored comprehensively. The stability in the ferromagnetic state (FM) has been ensured by energy released from optimized structures and enthalpy of formation (ΔH). The Heisenberg classical model has been used to calculate Curie temperature (Tc). The band structures (BS), as well as densities of states (DOS), are analyzed to explore half-metallic ferromagnetism and 100% spin polarization. The Δx(pd) (exchange energy) overcome ΔCF (Crystal field energy) because of ferromagnetism prompted by strong hybridization. The negative Δx(pd) and exchange constant N0 β reduced exchange energy that satisfies the double exchange model. The thermoelectric properties of the studied compounds are elaborated by estimating electrical conductivity, thermal conductivity, and the Seebeck coefficient. The increase in power factor with the CaFe2 S4 has been noted while other spinels have very low power factor. Highlights: Room temperature ferromagnetism, and thermoelectric behavior of CaZ2 S4  (Z = Ti, V, Cr, Fe) for spintronic applications. The studied compounds were computed to explore half-metallic ferromagnetism and 100% spin polarization. The exchange energy overcome crystal field energy due to ferromagnetism prompted by strong hybridization. In terms of thermoelectric properties, a comparatively larger power factor for the compound CaFe2 S4  has been observed.